Ruptured pyometra with peritonitis - P Keerthi Bharathi1 , C Vikas2 , T Ramesh3 (Perspectives In Medical Research, 2017)
Pyometra is the accumulation of purulent material (pus) in the uterine cavity, and spontaneous perforation of pyometra resulting in generalized diffuse peritonitis is extremely uncommon. The clinical picture is similar to peritonitis arising from intestinal perforation. In most cases, a correct and definitive diagnosis can be made only by laparotomy. Only a few cases have been recorded in the English medical literature, most of which were associated with gynaecological malignancy. We have recently treated a patient with peritonitis due to ruptured pyometra, in which there was no evidence of malignancy or other cervical disease. This paper reports an additional case of spontaneous uterine rupture in an elderly postmenopausal woman presenting with an acute abdomen.